2013
DOI: 10.1074/jbc.m113.476283
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin 1 Channels Link Chemoattractant Receptor Signaling to Local Excitation and Global Inhibition Responses at the Front and Back of Polarized Neutrophils

Abstract: Background: Chemotaxis requires excitatory and inhibitory signals at the front and back of cells. PANX1 and P2Y 2 receptors provide local excitation at the front. Results: We found that PANX1 triggers A 2A receptor activation and inhibits chemotactic signaling at the back. Conclusion: PANX1 thus integrates excitatory and inhibitory signals that regulate chemotaxis at the front and back of cells. Significance: These findings suggest new strategies to modulate neutrophil chemotaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(132 citation statements)
references
References 42 publications
3
127
1
1
Order By: Relevance
“…We have previously demonstrated that neutrophil chemotaxis in response to chemokine receptor stimulation is regulated by cellular ATP release and autocrine purinergic signaling [3,8]. Breast cancer cells express the chemokine receptor CXCR4, and the CXCR4 receptor ligand SDF-1α has been reported to contribute to metastasis of breast cancer by recruiting cancer cells to secondary organs such as the lungs [27][28][29][30].…”
Section: Mda-mb-231 Cells Display Uncoordinated Motility Patternsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that neutrophil chemotaxis in response to chemokine receptor stimulation is regulated by cellular ATP release and autocrine purinergic signaling [3,8]. Breast cancer cells express the chemokine receptor CXCR4, and the CXCR4 receptor ligand SDF-1α has been reported to contribute to metastasis of breast cancer by recruiting cancer cells to secondary organs such as the lungs [27][28][29][30].…”
Section: Mda-mb-231 Cells Display Uncoordinated Motility Patternsmentioning
confidence: 99%
“…The released ATP stimulates P2Y2 receptors that contribute to gradient sensing and delineate the direction of cell migration [3,7]. Ectonucleotidases such as alkaline phosphatase, CD39, and CD73 convert the released ATP to adenosine, which promotes autocrine stimulation of A3 receptors at the front of cells and A2a receptors at the back [3,4,7,8]. Both receptors elicit excitatory and inhibitory feedback mechanisms, respectively, that maintain cell polarity and increase the migration speed of neutrophils in a chemotactic gradient field (Supplemental Fig.…”
Section: Breast Cancer Cells Express Ectonucleotidases That Promote Amentioning
confidence: 99%
See 3 more Smart Citations